2013
DOI: 10.1155/2013/102918
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract ofCordyceps militarisGrown on Germinated Soybeans Attenuates Dextran-Sodium-Sulfate- (DSS-) Induced Colitis by Suppressing the Expression of Matrix Metalloproteinases and Inflammatory Mediators

Abstract: The effect of Cordyceps militaris (CM) grown on germinated soybeans (GSC) in the inflammatory bowel disease (IBD) model was studied. To demonstrate the preventive effect of GSC extract in a dextran-sodium-sulfate- (DSS-) induced acute colitis mouse model, GSC was administered 2 days before DSS coadministration. GSC significantly suppressed DSS-induced disease activity index (DAI) as well as histopathological scores, compared to control or CM-treated group. To elucidate the anti-IBD activity of GSC, we checked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…In the animal-based studies, it was stated, that isoflavone intake may diminish the secretion or overexpression of tumor necrosis factor-α[ 11 , 13 , 33 ], interleukin (IL)-1β[ 11 ], IL-6[ 12 ], IL-12p40[ 12 ], interferon-γ[ 11 , 12 ], cyclooxygenase-2[ 34 ] and inducible nitric oxide synthase[ 13 , 35 ]. In animal model, while disease activity index (including inter alia body weight loss, diarrhea, gross bleeding) of colitis was assessed, isoflavone intake was also stated to be beneficial[ 13 ]. As a result, isoflavone was indicated among natural compounds positively influencing cytokines in inflammatory bowel diseases[ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the animal-based studies, it was stated, that isoflavone intake may diminish the secretion or overexpression of tumor necrosis factor-α[ 11 , 13 , 33 ], interleukin (IL)-1β[ 11 ], IL-6[ 12 ], IL-12p40[ 12 ], interferon-γ[ 11 , 12 ], cyclooxygenase-2[ 34 ] and inducible nitric oxide synthase[ 13 , 35 ]. In animal model, while disease activity index (including inter alia body weight loss, diarrhea, gross bleeding) of colitis was assessed, isoflavone intake was also stated to be beneficial[ 13 ]. As a result, isoflavone was indicated among natural compounds positively influencing cytokines in inflammatory bowel diseases[ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first study proving the association between dietary isoflavone intake and ulcerative colitis development, indicated, that isoflavone intake may be associated with an increased risk of the disease[ 10 ]. However, a number of animal-model studies indicated, that isoflavone intake may prevent exacerbations by inhibiting the colitis[ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cordyceps militaris (CM) extracts have been shown to exert strong anti-inflammatory and anticancer activities (Cho et al, 2007) and are widely used among traditional medicines in East Asia to treat inflammatory diseases. Since CM is difficult to obtain in large amounts due to the high unit cost of production, germinated soybeans were used as culture media for CM (Park & Park, 2013)…”
Section: Effect Of Therapeutic Intervention On Mmps and Timps In Expementioning
confidence: 99%
“…Currently, traditional treatments for UC include aminosalicylates (sulfasalazine or mesalazine) and immunosuppressants (glucocorticoids, azathioprine, and methotrexate), which can produce adverse effects when used over the long term [23]. Natural products and their derivatives have been proposed as a source for new drug research and development due to their broad spectrum of therapeutic effects and their less severe side effects [10,34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need to search for new therapeutic options that are effective and have fewer side effects. Thus, natural products and their chemical compounds have been proposed as candidates for the development of new drugs due to their broad therapeutic spectrum, low toxicity, low occurrence of side effects, and low cost [10].…”
Section: Introductionmentioning
confidence: 99%